THE EFFICACY OF PHYSICAL THERAPY INTERVENTIONS FOR ADULTS WITH CEREBELLAR DYSFUNCTION A SYSTEMATIC REVIEW. (International Journal of Physiotherapy, 2014)
Background: Physiotherapy is a well-accepted modality in the rehabilitation process of cerebellar dysfunction. Despite being commonly accepted as rehabilitation measure there is a need for scientific evidence to prove role of Physiotherapy in persons with cerebellar dysfunction. This study is an effort to systematically review the literature investigating the effectiveness of physiotherapy in adults with cerebellar dysfunction and to document treatment strategies currently employed in the physiotherapy management of this patient population.Methods: Four electronic databases were searched to source English language studies published up to 30th April 2014. Secondary searching of reference list was also undertaken. Studies were included in this review if their primary intervention was physiotherapy on adults with cerebellar dysfunction. Three independent reviewers were involved in this study. Each contributed to the study by analyzing data related to participants, interventions received and effectiveness of each intervention as measured in research articles. The relevant outcomes were described adopting a narrative synthesis.Results: Eleven studies were reviewed. Majority of studies (n=10) were case studies or case series. The average quality score was 1.9 (range 1-10). All studies reported positive outcomes of rehabilitation measures both from the scientific point of view and also from participants’ perspective. No meta-analysis was undertaken in this study.Conclusion: There is modest evidence that physiotherapy may have a positive effect on the various limited abilities of adults with cerebellar dysfunction. The outcome measures however need cautious interpretations due to otherwise low volume, quality and clinical applicability of the this aftermath as per the available evidences analyzed by the researchers. There is also a need of high-quality researches to be carried out.